Multiwavelength Observations of the Blazar VER J0521+211 during an Elevated TeV Gamma-Ray State - Adams CB (IOP Publishing Ltd, 2022)
We report on a long-lasting, elevated gamma-ray flux state from VER J0521+211 observed by VERITAS, MAGIC, and Fermi-LAT in 2013 and 2014. The peak integral flux above 200 GeV measured with the nightly binned light curve is (8.8 +/- 0.4) x 10(-7) photons m(-2) s(-1), or similar to 37% of the Crab Nebula flux. Multiwavelength observations from X-ray, UV, and optical instruments are also presented. A moderate correlation between the X-ray and TeV gamma-ray fluxes was observed, and the X-ray spectrum appeared harder when the flux was higher. Using the gamma-ray spectrum and four models of the extragalactic background light (EBL), a conservative 95% confidence upper limit on the redshift of the source was found to be z <= 0.31. Unlike the gamma-ray and X-ray bands, the optical flux did not increase significantly during the studied period compared to the archival low-state flux. The spectral variability from optical to X-ray bands suggests that the synchrotron peak of the spectral energy distribution (SED) may become broader during flaring states, which can be adequately described with a one-zone synchrotron self-Compton model varying the high-energy end of the underlying particle spectrum. The synchrotron peak frequency of the SED and the radio morphology of the jet from the MOJAVE program are consistent with the source being an intermediate-frequency-peaked BL Lac object.